Risk Factors and Predictive Analysis of Acute Severe Abdominal Pain After Hepatic Artery Infusion Chemotherapy in Patients with Hepatocellular Carcinoma - Li J; Shi C; Chen J; Zhao Y; Du J; Song J (Journal of Hepatocellular Carcinoma)
Jinpeng Li,1,* Congcong Shi,2,* Jiao Chen,1 Yue Zhao,3 Jiasheng Du,4,* Jinlong Song1 1Department of Interventional Therapy I, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, Shandong, 250117, People’s Republic of China; 2Depression Disorder Diagnosis and Treatment Center, Shandong Mental Health Center, Jinan, Shandong, 250014, People’s Republic of China; 3Medical Imaging Technology Program, Qingdao Binhai University, Qingdao, 266000, People’s Republic of China; 4Department of Oncology, Linqing People’s Hospital, Liaocheng, 252600, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinpeng Li, Department of Interventional Therapy I, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, No. 440, Jiyan Road, Huaiyin District, Jinan, Shandong, 250117, People’s Republic of China, Tel +86 531-67626412, Email Ljpxxx308@126.comPurpose: To investigate the incidence patterns and risk factors of acute abdominal pain following hepatic arterial infusion chemotherapy (HAIC) in liver cancer patients and develop a preliminary prediction model for post-HAIC abdominal pain.Patients and Methods: Four hundred hepatocellular carcinoma patients who underwent HAIC at the Affiliated Cancer Hospital of Shandong First Medical University from January 2021 to March 2023 were retrospectively analyzed. The patients were categorized into two groups (abdominal pain and no abdominal pain) based on the occurrence of acute moderate to severe abdominal pain within 24 h after HAIC. Univariate analysis was performed on data from the two groups. Statistically significant factors were subjected to logistic regression analysis to construct a preliminary prediction model, and the predictive performance was evaluated.Results: A total of 358 hAIC procedures were performed in 242 patients who met the inclusion criteria. Of the 242 eligible patients, 88 (36.4%) experienced moderate to severe abdominal pain, while 154 (63.6%) had no significant pain. Age, tumor diameter, distance between the tumor and liver capsule, presence of portal vein tumor thrombus, oxaliplatin preparation time, and oxaliplatin manufacturer were independent predictors of acute moderate to severe abdominal pain following HAIC. The final prediction model demonstrated good predictive ability with an area under the receiver operating characteristic curve of 0.795 (95% confidence interval: 0.740– 0.853).Conclusion: The model developed in this study effectively predicted the risk of acute moderate to severe abdominal pain following HAIC and may provide a basis for more precise prevention and intervention strategies in clinical practice.Keywords: hepatocellular carcinoma, hepatic arterial infusion chemotherapy, abdominal pain, risk factors